Betatron with Magnetic Biasing; Instruments and Experimental Techniques; Vol. 45, iss. 1 - Kasyanov (Kas'yanov) V. A. Valery Alekseevich; Furman E. G. Edwin Gugovich; Chakhlov V. L. Vladimir Lukianovich; Chertov A. S. (2002, 2002)
Title screen